Isolation and Characterization of the Novel Phages vB_VpS_BA3 and vB_VpS_CA8 for Lysing Vibrio parahaemolyticus - Yang, Meiyan; Liang, Yongjian; Huang, Shixuan; Zhang, Jumei; Wang, Jing; Chen, Hanfang; Ye, Yuanming; Gao, Xiangyang; Wu, Qingping; Tan, Zhiyuan (Frontiers in Microbiology, 2020)
Accumulating evidence has indicated that the multiple drug resistant Vibrio parahaemolyticus may pose a serious threat to public health and economic concerns for humans globally. Here, two lytic bacteriophages, namely vB_VpS_BA3 and vB_VpS_CA8, were isolated from sewage collected in Guangzhou, China. Electron microscopy studies revealed both virions taxonomically belonged to the Siphoviridae family with icosahedral head and a long non-contractile tail. The double-stranded DNA genome of phage BA3 was composed of 58648 bp with a GC content of 46.30% while phage CA8 was 58480 bp with an average GC content of 46.42%. In total, 85 putative open reading frames (ORFs) were predicted in the phage BA3 genome while 84 were predicted in that of CA8. All ORFs were associated with phage structure, packing, host lysis, DNA metabolism, and additional functions. Furthermore, comparative genomic features and phylogenetic analysis revealed that BA3 and CA8 represented different isolates but novel members of the family, Siphoviridae. Both host range tests and one-step growth curve revealed that CA8 may have more potential than BA3 for biocontrol of multidrug resistant V. parahaemolyticus.